Rhizobium meliloti nodA and nodB genes are involved in generating compounds that stimulate mitosis of plant cells - Schmidt, Jürgen (1988)
The nodB gene of Rhizobium meliloti encodes a 23.8-kDa protein that is conserved in several Rhizobium species. Monospecific polyclonal antibodies against NodB were used to localize this protein in the cytosol of R. meliloti and Escherichia coli cells containing nodABC genes. In comparison to the NodA and NodC proteins, NodB is synthesized in a disproportionately low amount. The NodA and NodB proteins are involved in generating small, heat-stable compounds that stimulate the mitosis of various plant protoplasts. Our experiments suggest that NodC is not involved in the synthesis of the factors. On the basis of their properties, we speculate that the factors are cytokinin-like substances.